ANALISIS SERAPAN KEBISINGAN DENGAN PEMASANGAN ROCK WOOL KETEBALAN 5 CM - Haryono S Huboyo; Mochtar Hadiwidodo; Suhardi Suhardi (TEKNIK, 2013)
The noise affects to working quality at the same degree as those to workforce and people health, therefore,appropriate noise control is indispensable. This study is aimed at evaluating of rockwool (5cm) absorptioncoefficient and analyzing its effectivity on noise control. The room for simulation is equipped with known noisesource. In this case a sound system instrument and portable fire pump were used. The tested noise frequencieswere in the range of human hearing threshold for which an equalizer instrument was used to identify the soundfrequencies.Based on this study, the rockwool absorption coefficients were 0.8, 0.96, 0.98, 0.82 for sound frequency of 500Hz, 1000 Hz, 2000 Hz and 4000 Hz respectively. By installing the rockwool on 37.97% of room area of 72 m2,this rockwool was able to reduce the noise intensity by 10.16 dBA, 10.75 dBA, 10.5 dBA, 9.58 dBA, 9.25 dBA forfrequency of 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz and multiple frequencies respectively.The rockwool is an effective sound absorber in noise control owing to have high absorption coefficient (almostunity) and ease for installment.